Relation between microalbuminuria and gene mutations in familial Mediterranean fever - Ergüven, Müferet; Emeksiz, Can; Deveci, Murat; Özlü, Sare Gülfem (The Turkish Journal of Pediatrics, 2008)
We aimed to investigate the urinary microalbumin level, which is a sensitive marker of glomerular function for establishing probable renal involvement in early stages of the disease in patients with familial Mediterranean fever (FMF), and to determine the relation between gene mutations of these cases and urinary microalbumin levels. Fifty patients with FMF who were admitted to our department and had been followed up in the pediatric rheumatology outpatient clinic for five years were included in the study. Diagnosis was based on Tel-Hashomer criteria. Gene mutations (M694V, V726A, M680I) and acute phase reactants were determined as supportive findings. Routine renal function tests with 24 hour urinary microalbumin levels and urinary microalbumin/creatinine ratios were evaluated. There was a statistically significant difference between the study and control groups in terms of microalbumin/creatinine ratios, whereas no difference was observed with respect to the other parameters. Comparison of subgroups (gene mutations) in terms of all parameters (age, age at diagnosis, duration of delay in treatment, glomerular filtration rate, tubular reabsorption of phosphorus, and microalbumin/creatinine ratios) showed no difference. We suggest measurement of urinary microalbumin levels at regular intervals in order to establish renal injury early and decrease related complications.